Analisa Peran Keluarga Dalam Pelibatan Budaya Anti Kekerasan Seksual pada Anak - Syahril Ramadhon Alamsyah; Boris Brahmono; M Agus Mariyanto; Novi Yatri Pratiwi (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
This article provides a comprehensive overview of the role of the family in engaging in a culture of anti-sexual violence against children. This study examines sexual violence against children, the prevalence and risk factors for various types of sexual violence and discusses public knowledge and perceptions of this violence. It also examines the role of the family in a culture of anti-sexual violence in children and examines critically the meaning of a culture of anti-sexual violence in children. The diversity of literature reviews is the main qualitative method in this article, accompanied by the main focus of studies on the role of the family in anti-violence in children, examines specific cultural factors that do not only focus on cultural factors in general, but must examine the culture of non-violence in the context of modern society and consensus on international standards on human rights which are recommendations for further research. Keywords: Family Role, Culture, sexual violence against children